2002
DOI: 10.1021/ol0258029
|View full text |Cite
|
Sign up to set email alerts
|

On the Reactivity of o-Lithioaryl Ethers:  Tandem Anion Translocation and Wittig Rearrangement

Abstract: [reaction: see text]. Allyl and benzyl 2-lithioaryl ethers, generated by bromine-lithium exchange in THF, undergo a new tandem anion translocation-[1,2]-Wittig rearrangement allowing the isolation of the corresponding benzylic alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…However, little is known about the nucleophilic additions or substitution reactions of -oxybenzyllithiums. Following our research in this field, [13] we have previously reported that -lithiobenzyl o-lithiophenyl ethers, generated from benzyl 2-halophenyl ethers by halogen-lithium exchange and further -lithiation, do not suffer Wittig rearrangement allowing their trapping with carboxylic esters and leading to benzo[b]furan derivatives(Scheme 2). [14] With all these results in mind, we have recently described that the Wittig rearrangement in -lithiobenzyl phenyl ether can be suppressed by a careful control of the reaction temperature, allowing the intermediate organolithium to be functionalized prior to suffering the expected [1,2]-Wittig rearrangement (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the nucleophilic additions or substitution reactions of -oxybenzyllithiums. Following our research in this field, [13] we have previously reported that -lithiobenzyl o-lithiophenyl ethers, generated from benzyl 2-halophenyl ethers by halogen-lithium exchange and further -lithiation, do not suffer Wittig rearrangement allowing their trapping with carboxylic esters and leading to benzo[b]furan derivatives(Scheme 2). [14] With all these results in mind, we have recently described that the Wittig rearrangement in -lithiobenzyl phenyl ether can be suppressed by a careful control of the reaction temperature, allowing the intermediate organolithium to be functionalized prior to suffering the expected [1,2]-Wittig rearrangement (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…The mixture darkened and was stirred at 0°C for 2 h. The reaction mixture was added dropwise to diethyl ether (50 mL), and the precipitate was collected by filtration and dried to give the product 12b as a yellow powder (190 mg, 73 %). Preparation of 1-Allyloxy-2-bromobenzene: [47] A solution of 2-bromophenol (1 equiv., 10.0 g, 58 mmol) in dry THF (20 mL) was added to NaH (60 % suspension in mineral oil) (2.3 g, 58 mmol) in dry THF (20 mL) at 0°C over 1 h. The reaction mixture was stirred at 0°C for 30 min to give a pale brown solution. Allyl bromide (10.5 g, 87 mmol) was added at 0°C.…”
Section: Tricarbonyl[(1-5-η)-1-(2ј-formylphenyl)-4-methoxy-24-cyclohmentioning
confidence: 99%
“…The solvent was removed under reduced pressure to afford 1-alloxy-2-bromobenzene as a clear liquid (10.7 g, 87 % [ ( 1 mmol) was dissolved in dry diethyl ether (5 mL) and cooled to -78°C under nitrogen. nBuLi (1.6  in hexanes, 6 mmol, 3.8 mL) was added and 1-(allyloxy)-2-lithiobenzene [47,48] was formed by stirring at -78°C for 30 min. Salt 8 (1.1 g, 3.0 mmol) was dissolved in dry dichloromethane (5 mL) and cooled to -100°C.…”
Section: Tricarbonyl[(1-5-η)-1-(2ј-formylphenyl)-4-methoxy-24-cyclohmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the migration of aryl groups from aryl benzyl ethers has received much less attention (Scheme 1, eq 2). 6 Our interest in this field 7 led us to report that -lithiobenzyl o-lithiophenyl ethers, generated from benzyl 2-halophenyl ethers, do not undergo Wittig rearrangement probably due to the reluctance of the o-lithiophenoxy ring to migrate (Scheme 1, eq 3). 8 At this point, we thought about the possibility of inhibiting the Wittig rearrangement from aryl -lithiobenzyl ethers without the requirement of the additional lithium atom at the aryl ring.…”
mentioning
confidence: 99%